Malignant granular cell tumour of floor of mouth (non-neural in origin) – A rare case report and review of literature - Anju Khairwa; Nadeem Tanveer (SAGE Open Medical Case Reports)
Five cases of non-neuronal granular cell tumours of the oral cavity are documented in the literature. Additionally, one case of a non-neuronal granular cell tumour with features of malignancy was described. A malignant granular cell tumour is a rare neoplasm and counterpart of a benign granular cell tumour. The cell of origin of the granular cell tumour was reported from the Schwann cell. Some granular cells originated from non-neural components and were negative for immunohistochemistry S100. Immunohistochemistry is required to confirm further and categorize ulcero-proliferative and erythematous polypoidal oral cavity lesions. These lesions can mimic squamous cell carcinoma, mucoepidermoid carcinoma and pyogenic granuloma in morphology. We are presenting a rare case of malignant granular cell tumour of non-neuronal origin on the floor of the mouth. To our knowledge, it is the first case of a malignant non-neuronal granular cell tumour.